Factores Asociados a Hemorragia Intraventricular En Neonatos Atendidos En Un Hospital de Segundo Nivel - Camacho, Miguel Ángel Martínez; Lira, Alberto Juárez; Cortéz, Ma. de los Ángeles López; Roque, Helios Mancera (European Scientific Journal, ESJ, 2017)
Intraventricular hemorrhage (HIV) is a complication in neonates. It originates in the subependymal germinal matrix. This area is irrigated by a network of poorly differentiated vessels without a basement membrane. Also, it is fragile and vulnerable to the hemodynamic instability of cerebral blood flow. It is an important risk factor for periventricular leukomalacia, ventriculomegaly, and hydrocephalus. These neurological pathologies can generate sequelae in the pediatric population such as cerebral palsy (CP). Objective: To identify the factors associated with HIV in neonates treated in the early intervention program of the hospital of specialties of the child and the woman of the Secretary of Health of the State of Querétaro (HENMSESEQ). Material and Methods: Through the review of the clinical files, the factors associated with HIV present in the children attended to in the HENMSESEQ early intervention service were observed in 2015. Cases of HIV were corroborated by means of transfontanel ultrasound, statistical analysis with measures of central tendency, and comparison of the medians of children diagnosed with HIV and without diagnosis. Results: A group of 69 infants attended to in the early intervention program was studied. Out of them, 65.2% (45) were women and 34.3% (24) were men. They had a gestational age of 34.19 ± 4.22 weeks, birth weight of 2116.09 ± 859.36 g, and height of 44.06 ± 6.02 cm. Their stay in the Neonatal Intensive Care Unit (NICU) for the sample was 11.88 ± 16.84 days and they were 8.65 ± 12.20 days with invasive mechanical ventilation. There were 25 cases of HIV diagnosed by transfontanel ultrasound. Out of the 25 cases, 7 (10%) were HIV grade I, 14 (20%) II, 4 (5.7%) III, and no cases of grade IV were diagnosed. Using the Mann-Whitney U test, a difference was found between the groups of neonates diagnosed with HIV and without diagnosis in weeks of gestation, height, weight, APGAR, days of intubation, and days of stay in NICU.